A conversation analytical study of story-openings in advice-giving episodes in doctoral research supervision meetings. (April 2021) - Thanh Ta, Binh
Interactional functions of story-opening in everyday conversations across different languages have been widely examined in Conversation Analysis (CA). However, there is a paucity in research on story-openings in institutional talk. This paper addresses this research gap by examining how story-opening contributes to advice-giving in doctoral research supervision. It draws on a data corpus of 57 storytelling sequences produced by six supervisors during 25 hours of video-recorded supervision meetings at an Australian university. The analysis shows that story-opening supports the on-going advice-giving activity in two ways. First, it invokes the supervisor's knowledge and experience, which functions to strengthen the advice under way. Second, it works toward building a joint understanding with the student, thereby serving the supervisor's pursuit of the student's acceptance of advice. These findings have significant implications for research on storytelling in institutional interaction, advice and supervision practices.